Xylitol candies in caries prevention: results of a field study in Estonian children - Alanen P, Isokangas P, Gutmann K (Blackwell Synergy, 2000)
All field studies have unequivocally reported significant reductions in dental caries occurrence associated with the use of chewing gum containing xylitol. No other xylitol products besides chewing gum have so far been tested in field trials. A 5-year follow-up study with 2- or 3-year xylitol consumption periods began in Estonia in 1994 with 740 10-year-old children in 12 schools at baseline examinations. For the study, 3 clusters each including 3–5 schools were formed on the basis of baseline caries experience. The products were used under the supervision of the teachers 3 times per day during school days but not during weekends or during the 3-month summer holiday. The daily dose of xylitol was 5 g in all groups.